Komitmen Karyawan pada Penggabungan Organisasi Perguruan Tinggi - Stefanus Khrismasagung Trikusumaadi; Noviana Dewi (Pusat Riset dan Inovasi Nasional, 2025)
Organizational commitment in higher education institutions plays an important role in improving the quality of education. The demands and needs of society for the quality of education are aligned with organizational commitment. On the other hand, the merger of universities is also a strategic step in improving the quality of education. At this point, the merger of organizations can influence the work commitment of its employees, with various moderating factors. This study aims to describe how organizational commitment is, especially on post-merger period. By using 5 dimensions of organizational commitment, the differences in commitment in each group are tested quantitatively. Of the five dimensions of organizational commitment, namely: affective commitment, ongoing commitment (active), ongoing commitment (passive), normative commitment, and value commitment, there are significant differences in ongoing commitment (active) and values. The implication of this finding is that there is no common orientation towards career and shared values ​​after the merger.